1996
DOI: 10.1111/j.1460-9592.1996.tb00452.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of sevoflurane to halothane in paediatric surgical patients: results of a multicentre international study

Abstract: Induction, emergence and recovery characteristics were compared during sevoflurane or halothane anaesthetic in a large (428) multicentre, international study of children undergoing elective inpatient surgical procedures. Two hundred and fourteen children in each group underwent inhalation induction with nitrous oxide/oxygen and sevoflurane or halothane. Incremental doses of either study drug were added until loss of eyelash reflex was achieved. Steady state concentrations of anaesthesia were maintained until t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(69 citation statements)
references
References 24 publications
4
65
0
Order By: Relevance
“…Recovery time was similar for both groups, means being 11 and 12 minutes for each group respectively. This finding is similar to several reports of general anesthesia procedures in different medical specialties where the combination propofol-sevoflurane is used for GA. 31 The results of this study showed that 80% of the total sample of healthy children required greater than 120 minutes to complete the dental procedures, whereas most (67.5%) of the MCDD children required less than 120 minutes of DGA. It is important to note that there was not a statistical difference when comparing the number of teeth extracted in both groups.…”
Section: Discussionmentioning
confidence: 85%
“…Recovery time was similar for both groups, means being 11 and 12 minutes for each group respectively. This finding is similar to several reports of general anesthesia procedures in different medical specialties where the combination propofol-sevoflurane is used for GA. 31 The results of this study showed that 80% of the total sample of healthy children required greater than 120 minutes to complete the dental procedures, whereas most (67.5%) of the MCDD children required less than 120 minutes of DGA. It is important to note that there was not a statistical difference when comparing the number of teeth extracted in both groups.…”
Section: Discussionmentioning
confidence: 85%
“…4 Studies of sevoflurane in adults and healthy children suggest that it may have significant advantages over halothane in children and infants with heart disease. [5][6][7] Russell and colleagues 3 demonstrated that sevoflurane may have haemodynamic advantages over halothane during the induction and maintenance of anaesthesia in infants and children with congeni- They observed a 25% decrease in systolic blood pressure in the halothane group versus a 15% decrease in the sevoflurane group and a 60% incidence of dysrhythmias in the halothane group versus none in the sevoflurane group. In our study the blood pressure and heart rate findings revealed no significant differences between the control group and either the acyanotic or cyanotic groups.…”
Section: Discussionmentioning
confidence: 96%
“…hexafluoroisopropanol (HFIP) [33], or changes in renal plasma flow. More recently, it has been observed that maximum fluoride concentrations do not exceed 20 mmol.l 21 in children undergoing sevoflurane anaesthesia and they are therefore unlikely to be at risk from renal toxicity [34,35]. Despite some early misgivings [33], sevoflurane is now well established as the agent of choice for inhalational induction in both adults and children.…”
Section: Fluoridementioning
confidence: 99%